The Effect of Utilization of Sweet Potato Flour as Energy Source of Broiler Feed at Finisher Period to Carcass Weight, Chest Weight, Thigh Weight and Abdominal Fat - Nonok Supartini (Jurnal Ilmu dan Teknologi Hasil Ternak (JITEK), 2011)
The objective of current research is was to know the effect of feeding sweet potato flour as a source of energy to carcass weight, chest weight, thigh weight, and abdominal fat.The material of the research were 80 finisher male broiler with initial weight of 963.37 Â± 31.23 g. Completely Randomized Design (CRD) used for research method which consisted of 4 treatment, namely feeding without sweet potato flour (P0), with concentration of sweet potato flour of 10% (P1), 20% (P2) and 30% (P3).The parameter of research were carcass weight, chest weight,thigh weight and abdominal fat. The results showed that the gift effect of sweet potato flour to carcass weight were P0 1199.4%; P1 1138.98%; P2 1076.6; P3 1038.2; chest weight of P0 358.08; P1 366.6; P2 337.8; and P3 323.4%; thigh weight of P0 479.8; P1 472.94; P2 468.4; and P3 442; and abdominal fat of P0 33.2; P1 35.6; P2 25.4; P3 27.8. It could be concluded that the concentration of 10% sweet potato flour from total feeding gave the best treatment. Â  Keywords : sweet potato flour, carcass weight, chest weight, thigh weight, abdominal fat Â